Determinação de resíduos de ditiocarbamatos, empregando cromatografia gasosa acoplada a espectrometria de massas, em erva-mate (Ilex paraguariensis) produzida na América do Sul - Balbinot, Priscila Dotto Rosa (2022)
Dithiocarbamates (DTC) fungicides have characteristics related to high instability when in the presence of moisture and oxygen, thus requiring special preparation of the sample to be worked on, as well as the development and validation of an individual method for analysis of the generated compounds. In this work, an individual method for the determination of DTC in yerba mate was miniaturized and validated, based on the acid hydrolysis of the sample in the presence of tin chloride II, purification of the extract and subsequent analysis of the carbon disulfide (CS2) generated using gas chromatography–mass spectrometry (GC-MS). The optimization conditions were evaluated through miniaturization in the sample extraction process, based on the amount of sample, volume of extracting solvent and acid solution and the stirring time during the hot bath. These conditions were compared to those already described in the literature. As it is a complex matrix, an extract purification step was carried out through the dispersive solid phase extraction (d-SPE) process using primary and secondary amine (PSA) as sorbents, graphitized carbon (GCB) in addition to magnesium sulfate (MgSO4) as a drier. For the method validation study, the following parameters were evaluated: linearity, matrix effect, limit of detection (LOD) and limit of quantification (LOQ), precision and accuracy. Within the results obtained in the validation study, the LOD was established at 0.05 mg L-1 CS2, and the LOQ at 0.1 mg kg-1 CS2. The coefficient of determination (r2) obtained through the analytical curves was r2 > 0.99. The results obtained through the precision study were acceptable values with RSDr ≤11.2% and RSDpi ≤19.4% and, as well as the recoveries, in the range of 71.3 to 118.2%. The matrix effect calculated was -5.1%, which is within acceptable values for determining trace levels of contaminants. The validation parameters are in accordance with those described in DG-SANTE (2019) and, therefore, suitable for the determination of DTC in yerba mate. The validated method proved to be faster, simpler, and cheaper when compared to the traditional method described in the literature and quite effective for determining DTC in yerba mate. The miniaturized method was applied to 58 samples produced and sold in southern Brazil, 3 produced in Brazil and exported to Uruguay, and 4 produced in Argentina and sold in Brazil. Of the 65 herb samples that were used for the monitoring study, 33.8% had detectable levels of CS2, and 14% had concentration levels higher than the LOQ.